Perbandingan Pemahaman Konsep Matematis Siswa Yang Mendapatkan Metode Pembelajaran PSI Dengan Konvensional - Mubarika, Melinda Putri (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
This research used two models of learning they were methods personalized system of instruction (PSI) and the conventional learning models. This paper about contains a study on the comparison of mathematical concept understanding ability improvement among students who get a personalized system of instruction (PSI) methods with the conventional learning models. The results of this research, that increased the ability of understanding the mathematical concepts among students who get the personalized system of instruction methods learning is better than students who get conventional learning models. The attitudes of students about personalized system of instruction methods learning a positive indicated attitude and good interpretation.